Aderoidnye faktory v regional'nom razvitii Kaliningradskoj oblasti [The aderoid factors in the development of the Kaliningrad region] - Pogrebnyakov Pavel (Балтийский регион, 2011)
This article analyses the factors of the development of the Kaliningrad region. Expanding G. M. Fedorov’s complex analysis, the author identifies a new independent class of factors (aderoid factors) that have a significant impact on the regional development and are subject to an independent study. The analysis of aderoid factors makes it possible to create a management system that would change the sign of the factor from minus to plus or vice versa and block the model regression process.